Wartime Sexual Acts as Prosecutable War Crimes - Oikya, Upal Aditya (Díké - A Márkus Dezső Összehasonlító Jogtörténeti Kutatócsoport folyóirata, 2021)
Human history is littered with the mass rape of women particularly as a military strategy in warfare, dating back centuries from ancient Greek, Roman, and Hebrew concubines through the Middle Ages to the 20th century ‘comfort women’ of the 2nd World War. Ancient literature explicitly refers to rape or the seizure of vanquished women, who were regarded as the enemy’s property, to become wives, servants slaves, or concubines. The plight of women worsened in the twentieth century when civilian women suffered the most consequences of armed conflicts including rape. Rape served as an oppressive and humiliating tool to severe family identity to dominate, demoralize, and destroy the entire enemy society and way of life. In the past, there appeared to be no international law that specifically dealt with rape in armed conflicts. This was caused by the ambivalent relationship between the law of armed conflict and gender-based crimes. Rape was overlooked as an unfortunate yet inevitable by-product of war. Both international humanitarian and human rights laws did not initially recognize rape as a serious war crime and a fundamental breach of human rights. This deafening legal silence and gap are being addressed through an ongoing evolutionary process by criminalizing wartime predatory sexual acts as a war crime, crimes against humanity, and even genocide. However, with the developments of international law and its practice, for the first time in the history, mass rape and sexual enslavement in the time of war be regarded as ‘crimes against humanity’ in a landmark ruling from the Yugoslav War crime tribunal in the Hague on 22 February 2001. But, even before that, some prior legal instruments for example the Lieber Code, promulgated during the American Civil War regarded [wartime] rape as war crime with capital punishment. Thus, this paper aims to analyze how the historical legal instruments have articulated the extend of criminality and culpability of wartime rapes and other sexual violence and their nexus with crimes of humanity, genocide, and war crimes within the corpus of international norms and criminal prohibitions as well as the historical development of wartime sexual acts as prosecutable war crimes.